Cerium-doped zinc-zirconium solid solution catalyst as well as preparation method and application thereof

By doping cerium into the zinc-zirconium solid solution catalyst, the electronic structure and strong acid sites of the catalyst are improved, and the problems of low conversion, poor selectivity and low stability in the production of diphenyl carbonate in the prior art are solved, and the performance of high efficiency and high selectivity is achieved.

CN119500097AActive Publication Date: 2025-02-25CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411619916.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The prior art has problems such as low conversion, poor selectivity and low stability in the production of diphenyl carbonate, especially when using precious metal palladium as a catalyst.

Method used

A cerium-doped zinc-zirconium solid solution catalyst was developed to improve the electronic structure of the catalyst and increase the strong acid site by doping the cerium element into the zinc-zirconium solid solution, thereby improving the phenol conversion, diphenyl carbonate selectivity and the service life of the catalyst.

Benefits of technology

High phenol conversion, excellent diphenyl carbonate selectivity and high catalyst life are achieved, the process flow is simplified, energy consumption is reduced, and the use of precious metals is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500097A_ABST
    Figure CN119500097A_ABST
Patent Text Reader

Abstract

The invention provides a cerium-doped zinc-zirconium solid solution catalyst as well as a preparation method and application thereof. The chemical formula of the catalyst is CeaZnbZrcOx, a is greater than or equal to 0 and less than or equal to 4, b is greater than or equal to 1 and less than or equal to 4, c is equal to 4, and x represents that oxygen vacancies exist in the catalyst; the catalyst has a first diffraction peak with 2 theta ranging from 28.46 degrees to 30.48 degrees, a second diffraction peak with 2 theta ranging from 47.50 degrees to 50.81 degrees, a third diffraction peak with 2 theta ranging from 56.27 degrees to 60.43 degrees and a fourth diffraction peak with 2 theta ranging from 32.98 degrees to 35.42 degrees, and the intensity ratio of the first diffraction peak to the second diffraction peak to the third diffraction peak to the fourth diffraction peak is (2.2-3.1): (1.1-1.4): (0.9-1.2): 1. The cerium-doped zinc-zirconium solid solution catalyst provided by the invention can catalyze carbon dioxide and phenol to synthesize diphenyl carbonate, and has high phenol conversion rate, excellent diphenyl carbonate selectivity and long catalyst life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of petrochemical industry, and in particular to a cerium-doped zinc-zirconium solid solution catalyst and a preparation method and application thereof. Background Art

[0002] The cerium-doped zinc-zirconium solid solution catalyst provided by the present invention belongs to the field of petrochemical industry and can be used as a catalyst to catalyze the reaction of carbon dioxide and phenol to synthesize diphenyl carbonate. Diphenyl carbonate is mainly used in the production of polycarbonate and is also widely used in the fields of solvents, plasticizers, medicines, pesticides, etc.

[0003] At present, the traditional large-scale production processes of diphenyl carbonate mainly include phosgene method, oxidative carbonylation method and transesterification method. Among these synthetic routes, the phosgene method uses toxic phosgene as a raw material, which poses a threat to the environment and the health of operators. This route also requires a large amount of NaOH to neutralize the inorganic acid produced, generating a large amount of waste salt and wastewater. For the oxidative carbonylation process, the precious metal palladium must be used as a catalyst during the synthesis process, and a variety of co-catalysts (anhydrous copper acetate, tetrabutylammonium bromide and hydroquinone, etc.) must also be added. The precious metal Pd 2+ The reduction and agglomeration of the catalyst will lead to the deactivation of the catalyst, making it difficult to recycle the catalyst. The raw materials used in the transesterification reaction are easily available and non-toxic, and only methanol is produced as a byproduct in the process. However, dimethyl carbonate is both a raw material and a product in the transesterification reaction. At the same time, the reaction equilibrium constant is small. The limitations of chemical equilibrium and chemical activity mean that the transesterification is still in the laboratory research stage.

[0004] In order to solve the defects of the above preparation methods, using carbon dioxide as a C1 substrate to catalyze the formation of C-O bonds has always been a challenging task in organic synthesis and catalytic research. The direct catalytic synthesis of diphenyl carbonate by carbon dioxide and phenol not only avoids the drawbacks of the above production routes, but also realizes the comprehensive utilization of carbon dioxide resources. It is considered to be an ideal way to produce diphenyl carbonate. The synthesis of diphenyl carbonate by carbon dioxide and phenol meets the requirements of the current development of green chemistry. Therefore, the development of a reaction system suitable for this catalytic reaction will surely accelerate the process of advancing diphenyl carbonate from the experimental development stage to industrial production.

[0005] At present, a series of catalysts have been reported, including metal Lewis acid catalysts (such as ZnCl2, CoCl2, AlBr3) (Li ZH, Qin ZF, Zhu HQ, Wang JG, Chem. Lett., 2006, 35, 784-785; FanG Z, Wang ZG, Zou B, Wang M, Fuel Proc. Tech., 2011, 92, 1052-1055; Wang SL, Jiang N, Peng JL, Yang P, Cui CX, Niu HY, Zhang QY, Wang JJ, ACSSustain. Chem. Eng., 2022, 10, 12689-12697) and metal-hydrochloric acid complexes (Fan GZ, Wang M, Duan ZX, Wan MH, Fang T, Aust. J. Chem, 2012, 65, 1667-1673), supported catalysts (such as MCl X / SiMCM-41, Fe3O4@SiO2−ZnBr2, Zn / SiO2−TiO2) (Su KM, Li ZH, Cheng BW, RenY L, Catal. Commun., 2008, 9, 1666-1670; Su K, Li Z, Cheng B, Ren Y, Yu L,Wang F, Kinet. Catal., 2010, 51, 359-363; Wang M, Duan ZX, Fang T, Wang MH,Fan GZ, Adv. Mat. Res., 2011, 391-392, 1235-1238; GZ Fan, SS Luo, Q Wu, TFang, JF Li, GS Song, RSC Adv., 2015, 5, 56478-56485; Wang M, Duan ZX, FangT, Wang MH, Fan GZ, Adv. Mat. Res., 2011, 391-392, 1235-1238). Compared with the problem that ZnCl2 and other catalysts are difficult to separate, recycle and reuse when dissolved in the reaction system, supported catalysts have the advantages of easy separation of products and simple recovery, which can simplify the process flow and reduce energy consumption. At present, Zn-based catalysts are mainly supported, and K2CO3, triethylamine and other additives are used to modify them to improve catalytic performance. There are problems such as low conversion rate, poor selectivity, low stability and easy deactivation. When metal Lewis acids are loaded on carriers, there are also problems such as easy loss of active components and low stability.

[0006] Therefore, developing a catalyst for preparing diphenyl carbonate with high conversion rate and stability has become a research direction in this field. Summary of the invention

[0007] The invention provides a cerium-doped zinc-zirconium solid solution catalyst, which can catalyze carbon dioxide and phenol to synthesize diphenyl carbonate, and has high phenol conversion rate, good diphenyl carbonate selectivity and high catalyst life.

[0008] The present invention provides a method for preparing the catalyst, which achieves the technical effect of a simple and easy preparation process.

[0009] The invention provides a method for preparing diphenyl carbonate, which achieves technical effects of high conversion rate and selectivity.

[0010] The present invention provides a cerium-doped zinc-zirconium solid solution catalyst, wherein the chemical formula of the catalyst is Ce a Znb Zr c O x , where 0≤a≤4, 1≤b≤4, c=4;

[0011] The catalyst has a 2θ value of 28.46 o ~30.48 o The first diffraction peak, 2θ is 47.50 o ~50.81 o The second diffraction peak, 2θ is 56.27 o ~60.43 o The third diffraction peak, and 2θ is 32.98 o ~35.42 o The fourth diffraction peak of the optical spectrum is as follows, and the intensity ratio of the first diffraction peak, the second diffraction peak, the third diffraction peak and the fourth diffraction peak is (2.2-3.1):(1.1-1.4):(0.9-1.2):1.

[0012] The cerium-doped zinc-zirconium solid solution catalyst as described above, wherein the catalyst is prepared by a method comprising the following process:

[0013] The pH value of the aqueous solution including Ce, Zn and Zr elements is adjusted to be greater than or equal to 10, the obtained mixed system is subjected to aging treatment and solid-liquid separation treatment in sequence, and the obtained solid phase product is subjected to calcination treatment to obtain the catalyst.

[0014] The present invention also provides a method for preparing a cerium-doped zinc-zirconium solid solution catalyst, which can be used to prepare any of the above-mentioned cerium-doped zinc-zirconium solid solution catalysts. The method comprises the following steps:

[0015] The pH value of the aqueous solution including Ce, Zn and Zr elements is adjusted to be greater than or equal to 10, the obtained mixed system is subjected to aging treatment and solid-liquid separation treatment in sequence, and the obtained solid phase product is subjected to calcination treatment to obtain the catalyst.

[0016] The method for preparing the cerium-doped zinc-zirconium solid solution catalyst as described above, wherein the molar ratio of Ce / (Zn+Zr) is 0.125-0.8; and / or,

[0017] In the aqueous solution, the concentration of total metal elements is 0.150-0.225 mol / L.

[0018] The method for preparing the cerium-doped zinc-zirconium solid solution catalyst as described above, wherein the pH value of the aqueous solution including the Ce element, the Zn element and the Zr element is adjusted to 10-11.

[0019] The method for preparing the cerium-doped zinc-zirconium solid solution catalyst as described above, wherein the treatment temperature of the aging treatment is 70-90° C., and the treatment time is 2-4 hours.

[0020] The preparation method of the cerium-doped zinc-zirconium solid solution catalyst as described above, wherein the treatment temperature of the calcination treatment is 500-600° C., the treatment time is 2-4 hours, and the heating rate is 1-3° C. / h.

[0021] The method for preparing the cerium-doped zinc-zirconium solid solution catalyst as described above, wherein before the solid phase product is calcined, the method further includes drying the solid phase product, the treatment temperature of the drying treatment is 100-120° C., and the treatment time is 6-10 hours.

[0022] The present invention also provides a method for preparing diphenyl carbonate, wherein the method uses any one of the above-mentioned cerium-doped zinc-zirconium solid solution catalysts to catalyze the reaction of carbon dioxide and phenol to obtain diphenyl carbonate.

[0023] The method for preparing diphenyl carbonate as described above, wherein the reaction temperature is 90-130° C., the reaction pressure is 1-5 MPa, and the reaction time is 4-8 h.

[0024] The cerium-doped zinc-zirconium solid solution catalyst of the present invention improves the electronic structure of the catalyst and effectively increases the strong acid sites in the catalyst by doping cerium into the zinc-zirconium solid solution, so that the catalyst has a higher phenol conversion rate, better diphenyl carbonate selectivity and a longer service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced one by one below. Obviously, the drawings in the following description are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 are X-ray diffraction patterns of catalysts A1-A7 and catalyst B1;

[0027] Figure 2 are the Raman images of catalyst A1 and catalyst B1;

[0028] Figure 3 are the EPR diagrams of catalyst A1 and catalyst B1;

[0029] Figure 4 Py-IR graphs of catalyst A1 and catalyst B1;

[0030] Figure 5 NH3-TPD diagrams of catalyst A1 and catalyst B1;

[0031] Figure 6 Graph showing phenol conversion rates of catalysts A1-A7 and catalyst B1 at different reaction pressures;

[0032] Figure 7 The selectivity diagram of diphenyl carbonate of catalysts A1-A7 and catalyst B1 at different reaction pressures;

[0033] Figure 8 The yield of diphenyl carbonate of catalysts A1-A7 and catalyst B1 under different reaction pressures. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The cerium-doped zinc-zirconium solid solution catalyst provided by the invention can be used as a catalyst to catalyze the reaction of carbon dioxide and phenol to synthesize diphenyl carbonate.

[0036] At present, the catalyst used to synthesize diphenyl carbonate has the problems of low conversion rate, poor selectivity, low stability and easy deactivation. The inventors doped cerium into zinc-zirconium solid solution to obtain the above-mentioned catalyst, which improved the electronic structure of the catalyst and effectively increased the strong acid sites in the catalyst, so that the catalyst has a higher phenol conversion rate, better diphenyl carbonate selectivity and a longer service life.

[0037] Based on this, the first aspect of the present invention provides a cerium-doped zinc-zirconium solid solution catalyst, the chemical formula of which is Ce a Zn b Zr c O x , where 1≤a≤4, 1≤b≤4, c=4, x represents the presence of oxygen vacancies in the catalyst, 1≤x≤2, and the exact value cannot be accurately determined using existing technical means; and the catalyst has a 2θ value of 28.46 o ~30.48 o The first diffraction peak, 2θ is 47.50 o ~50.81 o The second diffraction peak, 2θ is 56.27 o ~60.43 o The third diffraction peak, and 2θ is 32.98o ~35.42 o The fourth diffraction peak, and the intensity ratio of the first diffraction peak, the second diffraction peak, the third diffraction peak and the fourth diffraction peak is (2.2~3.1):(1.1~1.4):(0.9~1.2):1.

[0038] The inventors found that the cerium-doped zinc-zirconium solid solution catalyst provided by the present invention has the technical effect of high conversion rate and selectivity and is not easy to deactivate. The inventors speculated based on the above phenomenon that the reason may be that, firstly, the doping of cerium element improves the electronic structure of the catalyst and effectively increases the strong acid sites in the catalyst while increasing the concentration of oxygen vacancies; secondly, the above XRD characteristics indicate that there are uniformly dispersed Zn / Ce-Ov-Zr sites in the catalyst, which can promote the synergistic effect between Zn, Ce and Zr, which is beneficial to CO2 conversion and diphenyl carbonate selectivity, so that the cerium-doped zinc-zirconium solid solution catalyst provided by the present invention has the technical effect of high conversion rate and selectivity and is not easy to deactivate.

[0039] The present invention improves the electronic structure of the catalyst by doping cerium into a zinc-zirconium solid solution, while effectively increasing the strong acid sites in the catalyst, so that the catalyst has a higher phenol conversion rate, better diphenyl carbonate selectivity and a longer service life.

[0040] In detail, the catalyst provided in the first aspect of the present invention can also be prepared by a method comprising the following process: adjusting the pH value of an aqueous solution comprising Ce elements, Zn elements and Zr elements to be greater than or equal to 10, subjecting the obtained mixed system to aging treatment and solid-liquid separation treatment in sequence, and subjecting the obtained solid phase product to calcination treatment to obtain the catalyst provided in the first aspect of the present invention.

[0041] Among them, the aqueous solution including Ce element, Zn element and Zr element means that the solution uses water as solvent and contains cerium element, zinc element and zirconium element at the same time. It is understandable that in order to make the aqueous solution have a higher concentration of the above three elements, the soluble salts of the above three elements can be used to dissolve in water to obtain an aqueous solution including a cerium metal source, a zinc metal source and a zirconium metal source. The present invention does not limit the specific selection of the soluble salts of the above three elements. In detail, nitrates, sulfates or halides of cerium, zinc and zirconium can be used as cerium metal sources, zinc metal sources and zirconium metal sources, respectively. In a preferred embodiment, nitrates and sulfates of cerium, zinc and zirconium are selected as cerium metal sources, zinc metal sources and zirconium metal sources, respectively.

[0042] When the pH value of the aqueous solution including the cerium metal source, the zinc metal source and the zirconium metal source is adjusted to be greater than or equal to 10, the cerium element, the zinc element and the zirconium element in the aqueous solution are converted into hydroxide precipitates and separated from the liquid phase system.

[0043] The present invention does not limit the way to adjust the pH value of the aqueous solution to be greater than or equal to 10, and conventional methods in the art can be used. Specifically, it can be achieved by adding an alkaline substance to the above-mentioned aqueous solution. The present invention does not limit the specific selection of the alkaline substance, and at least one of alkali metal hydroxides, alkali metal carbonates, and ammonia water can be selected. In a preferred embodiment, the alkaline substance is ammonia water. The use of ammonia water to adjust the pH value of the aqueous solution can achieve the effect of complete precipitation of the hydroxide by regulating the hydrolysis rate principle of the precipitant. If sodium hydroxide or sodium carbonate is used to adjust the pH value, incomplete precipitation may occur or agglomeration may occur, affecting the preparation of the cerium-doped zinc-zirconium solid solution catalyst.

[0044] After the cerium, zinc and zirconium elements in the aqueous solution are converted into hydroxide precipitates, the mixed system including the solid hydroxide precipitate and the liquid solution can be aged. The aging treatment includes continuous stirring of the mixed system, and the aging treatment ends when the stirring stops. This treatment can achieve the technical effect of improving the specific surface area and pore size of the catalyst through the principle of phase change of the catalyst precursor, thereby improving the catalytic performance.

[0045] The mixed system obtained by the aging treatment is subjected to a solid-liquid separation treatment to obtain an aged solid phase material. The solid phase material is subjected to a calcination treatment to obtain the catalyst provided by the present invention. During the calcination process, a phase change and an oxidation-reduction reaction occur to form a catalyst having the above characteristics. The present invention does not limit the specific treatment conditions of the calcination reaction, and the catalyst provided by the first aspect of the present invention can be obtained.

[0046] The second aspect of the present invention provides a method for preparing a cerium-doped zinc-zirconium solid solution catalyst, which comprises the following steps: adjusting the pH value of an aqueous solution comprising Ce, Zn and Zr elements to be greater than or equal to 10, sequentially subjecting the obtained mixed system to aging treatment and solid-liquid separation treatment, and calcining the obtained solid phase product to obtain a catalyst.

[0047] The meanings of the aqueous solution including Ce element, Zn element and Zr element, aging treatment, solid-liquid separation treatment and calcination treatment are the same as above and will not be repeated here.

[0048] The preparation method of the cerium-doped zinc-zirconium solid solution catalyst provided by the present invention uses simple and readily available reagents to prepare a catalyst with high conversion rate and selectivity and not prone to deactivation, has the advantages of simple process flow, mild conditions, and low cost, and is suitable for mass production.

[0049] In order to further improve the selectivity of the catalyst for diphenyl carbonate, the molar ratio of Ce / (Zn+Zr) in the aqueous solution including Ce, Zn and Zr elements can be 0.125-0.8, that is, the ratio of Ce element concentration to the sum of Zn and Zr element concentrations is 0.125-0.8. The appropriate element concentration ratio can produce a catalyst with a suitable element molar ratio, and the electronic structure and medium-strong acid sites of the catalyst with a suitable element molar ratio are further strengthened, so that the phenol conversion rate, diphenyl carbonate selectivity and service life of the catalyst are further increased. In a preferred embodiment, the molar ratio of Ce / (Zn+Zr) can be controlled to 0.2-0.4.

[0050] In order to achieve the purpose of uniform dispersion of Ce and Zn in ZrO2, the total metal element concentration in the aqueous solution including Ce, Zn and Zr can be 0.150-0.225 mol / L. If the total metal element concentration is lower than this range, the active sites in the prepared catalyst are reduced; if the metal element concentration is higher than this range, the aqueous solution is prone to phase separation. Controlling the total metal concentration within the above range can obtain the technical effect of uniformly dispersed Zn / Ce-Ov-Zr structure.

[0051] In order to further increase the phenol conversion rate, diphenyl carbonate selectivity and service life of the prepared catalyst, during the preparation of the above catalyst, the pH value of the aqueous solution including cerium, zinc and zirconium can be adjusted to 10-11. Controlling the pH within the above range can not only allow the three metal elements to completely form hydroxide precipitation, thereby improving the yield of the above preparation method, but also reduce the degree of redissolution of zinc hydroxide due to the formation of zincate due to excessively high pH, ​​so that more zinc elements enter the solid phase in the form of hydroxide, so that the prepared catalyst has a suitable metal element ratio, thereby having better application performance.

[0052] The inventors further found that when the aging treatment temperature is controlled to be 70-90°C and the treatment time is 2-4 hours, the obtained catalyst has better phenol conversion rate, diphenyl carbonate selectivity and service life. Based on the above phenomenon, the inventors speculate that the reason may be that the appropriate treatment temperature and treatment time can achieve performance optimization and stability improvement effects through thermodynamics and kinetics principles.

[0053] The inventors further found that when the treatment temperature of the calcination treatment is controlled to be 500-600°C, the treatment time is 2-4h, and the heating rate is 1-3°C / h, the obtained catalyst has better phenol conversion, diphenyl carbonate selectivity and service life. The inventors speculated that the reason may be that the appropriate treatment temperature, treatment time and heating rate can achieve the effect through the principle of phase transition and redox. In a preferred embodiment, the treatment temperature of the calcination treatment is 550°C, the treatment time is 3h, and the heating rate is 2°C / h.

[0054] In order to achieve the effect of removing moisture, the inventors found that before calcining the solid phase product, the solid phase product should also be dried. The drying temperature is 100-120°C and the treatment time is 6-10 hours.

[0055] The third aspect of the present invention provides a method for preparing diphenyl carbonate, which uses the cerium-doped zinc-zirconium solid solution catalyst provided by the first aspect of the present invention to catalyze the reaction of carbon dioxide and phenol to obtain diphenyl carbonate. Since the catalyst provided by the first aspect of the present invention has a high phenol conversion rate, a better diphenyl carbonate selectivity and a longer service life, the method for preparing diphenyl carbonate provided by the third aspect of the present invention has the characteristics of a high phenol conversion rate and a better diphenyl carbonate selectivity.

[0056] The inventors further discovered that when the cerium-doped zinc-zirconium solid solution catalyst provided in the first aspect of the present invention is used to catalyze the reaction of carbon dioxide and phenol, the reaction temperature is controlled to be 90-130°C, the reaction pressure is 1-5MPa, and the reaction time is 4-8h, a higher yield of diphenyl carbonate can be obtained.

[0057] The present invention is further described below through specific embodiments.

[0058] Examples 1-7 are preparations of cerium-doped zinc-zirconium solid solution catalysts with different cerium contents:

[0059] Example 1

[0060] Weigh 5mmol hexahydrated cerium nitrate, 5mmol hexahydrated zinc nitrate, and 20mmol hydrated zirconium oxynitrate, dissolve in 200mL deionized water and stir evenly to form a mixed solution with a metal ion concentration of 0.15mol / L. After stirring for 0.5h in a water bath at 80℃, slowly add 25wt% ammonia water to the precursor solution, and adjust the pH value of the aqueous solution to 11. After the addition is completed, keep it in a water bath at 80℃ for aging for 2h. The molecular formula is CeZnZr4O x Catalyst A1, wherein the molar ratio of Ce / (Zn+Zr) is 1:5.

[0061] Example 2

[0062] Weigh 10mmol of cerium nitrate hexahydrate, 5mmol of zinc nitrate hexahydrate, and 20mmol of zirconium oxynitrate hydrate, dissolve in 200mL of deionized water and stir evenly to form a mixed solution with a metal ion concentration of 0.175mol / L. The other preparation steps are the same as those in Example 1 to obtain Ce2ZnZr4O x Catalyst A2, wherein the molar ratio of Ce / (Zn+Zr) is 2:5.

[0063] Example 3

[0064] Weigh 15mmol of cerium nitrate hexahydrate, 5mmol of zinc nitrate hexahydrate, and 20mmol of zirconium oxynitrate hydrate, dissolve them in 200mL of deionized water and stir them evenly to form a mixed solution with a metal ion concentration of 0.20mol / L. The other preparation steps are the same as those in Example 1. The molecular formula is Ce3ZnZr4O x Catalyst A3, wherein the molar ratio of Ce / (Zn+Zr) is 3:5.

[0065] Example 4

[0066] Weigh 20mmol of cerium nitrate hexahydrate, 5mmol of zinc nitrate hexahydrate, and 20mmol of zirconium oxynitrate hydrate, dissolve them in 200mL of deionized water and stir them evenly to form a mixed solution with a metal ion concentration of 0.225mol / L. The other preparation steps are the same as those in Example 1 to obtain Ce4ZnZr4O x Catalyst A4, wherein the molar ratio of Ce / (Zn+Zr) is 4:5.

[0067] Example 5

[0068] Weigh 5mmol of cerium nitrate hexahydrate, 10mmol of zinc nitrate hexahydrate, and 20mmol of zirconium oxynitrate hydrate, dissolve them in 200mL of deionized water and stir evenly to form a mixed solution with a metal ion concentration of 0.175mol / L. The other preparation steps are the same as those in Example 1 to obtain CeZn2Zr4O x Catalyst A5, wherein the molar ratio of Ce / (Zn+Zr) is 1:6.

[0069] Example 6

[0070] Weigh 5mmol of cerium nitrate hexahydrate, 15mmol of zinc nitrate hexahydrate, and 20mmol of zirconium oxynitrate hydrate, dissolve them in 200mL of deionized water and stir them evenly to form a mixed solution with a metal ion concentration of 0.20mol / L. The other preparation steps are the same as those in Example 1 to obtain a mixture with a molecular formula of CeZn3Zr4O xCatalyst A6, wherein the molar ratio of Ce / (Zn+Zr) is 1:7.

[0071] Example 7

[0072] Weigh 5mmol of cerium nitrate hexahydrate, 20mmol of zinc nitrate hexahydrate, and 20mmol of zirconium oxynitrate hydrate, dissolve them in 200mL of deionized water and stir them evenly to form a mixed solution with a metal ion concentration of 0.225mol / L. The other preparation steps are the same as those in Example 1 to obtain a mixture with a molecular formula of CeZn4Zr4O x Catalyst A7, wherein the molar ratio of Ce / (Zn+Zr) is 1:8.

[0073] Comparative Example 1

[0074] Weigh 5 mmol of zinc nitrate hexahydrate and 25 mmol of zirconium oxynitrate hydrate, dissolve them in 200 mL of deionized water and stir them evenly to form a mixed solution with a metal ion concentration of 0.15 mol / L. The other preparation steps are the same as those in Example 1 to obtain a solution with a molecular formula of ZnZr5O x Catalyst B1, wherein the molar ratio of Zn / Zr is 1:5.

[0075] Test example

[0076] Catalyst evaluation

[0077] The catalyst samples obtained in Examples 1-7 and Comparative Example were characterized by X-ray diffractometer. Figure 1 Typically, taking the catalyst A1 obtained in Example 1 as an example, and comparing it with the catalyst of the comparative example, Figure 1 It can be seen that the XRD results show that the catalyst B1 and catalysts A1-A7 prepared by the present invention all show the characteristic diffraction peak of tetragonal ZrO2, and catalysts A1-A3, A5-A6 all form a solid solution structure, while A4 and A7 show the characteristic diffraction peaks of CeO2 and ZnO in the excessive doping. Compared with the standard XRD card of t-ZrO2 (JCPDS 88-1007), the characteristic peak of XRD of the catalyst B1 sample shifts to a high angle. This is because the atomic radius of Zn is smaller than the atomic radius of Zr. When Zn atoms partially replace Zr atoms in t-ZrO2, the lattice shrinks, and then the characteristic peak shifts to a high angle in the XRD spectrum. When Ce, which is larger than the atomic radius of Zr, is doped, the XRD spectra of catalysts A1-A4 shift to a low angle compared to catalyst B1. This characterization result shows that the present invention successfully prepares a cerium-doped zinc-zirconium solid solution catalyst.

[0078] Catalyst A1 and catalyst B1 were subjected to Raman tests, where the 149, 269, 312, 465 and 643 cm -1The Raman spectrum band at belongs to the tetragonal phase of ZrO2. The Raman analysis results are shown in Figure 2 After adding Zn to catalyst B1, the -1 The band at 550-620 cm-1 associated with oxygen vacancies was observed in the Raman graph. -1 The wide band of the region indicates that cerium doping further increases the number of oxygen defects in the solid solution compared to catalyst B1, which helps to activate the reactants during the reaction.

[0079] To further analyze the relative concentration of oxygen vacancies, EPR measurements were performed on catalysts A1 and B1. Unpaired electrons were captured in the EPR measurements. The results are shown in Figure 2. Figure 3 As shown in Figure 2, the signal intensity near g = 2.003 is positively correlated with the content of oxygen vacancies. The concentration of oxygen vacancies changes in the order of ZnCeZrO X >ZnZrO X , which is consistent with the Raman results and further proves that the introduction of Ce increases the number of oxygen vacancies in the solid solution.

[0080] In order to study the effect of catalyst acidity on DPC reaction performance, Py-IR test was carried out on catalyst A1 and catalyst B1. The results are shown in Figure 4 . Py-IR can be used to identify the acidity type of the catalyst. 1446cm -1 、1540cm -1 and 1491cm -1 The peaks at are attributed to Lewis coordinated pyridine (L), Brønsted coordinated pyridine (B) and Lewis+Brønsted coordinated pyridine (L+B). Figure 4 It can be seen that ZnCeZrO X The Lewis acid sites of (A1) are larger than those of ZnZrO X (B1) is much stronger. This shows that in the preparation of ZnCeZrO X When Ce is added, it not only increases the concentration of oxygen vacancies in the material, but also promotes electron rearrangement and interaction, thereby improving the electron acceptance capacity and Lewis acidity of the material.

[0081] In order to further analyze the effect of Lewis acid strength on DPC selectivity, NH3-TPD studies were conducted on catalysts A1 and B1. The results are shown in Figure 5 .Depend on Figure 5It can be seen that catalyst B1 is mainly composed of weak acid sites, while catalyst A1 has both weak acid sites and medium-strong acid sites, and the medium-strong acid sites are helpful for the synthesis of the target product. This shows that cerium doping effectively increases the acid sites of the catalyst while improving the electronic structure of the catalyst, thereby achieving an increase in the yield and selectivity of the target product.

[0082] Test Example 1

[0083] The catalytic performance of catalysts A1-A7 prepared in Examples 1-7 and catalyst B1 (as a comparative example) in synthesizing diphenyl carbonate from carbon dioxide and phenol was tested. The specific operation was as follows: a 100 mL high-pressure microreactor was used, catalysts A1-A7 were used as catalysts, 20 mmol phenol, 0.2 g catalysts A1-A7 and 10 mL CCl4 were added to the reactor, and after sealing, carbon dioxide was introduced into the reactor to replace the air in the reactor. After the reactor was heated to 120°C, carbon dioxide was introduced into the reactor to increase the pressure in the reactor to the reaction pressure, and then the air inlet valve was closed. The stirring reaction was continued for 6 hours and then the stirring was stopped. The reaction was then cooled to room temperature, the catalyst was separated by centrifugation, and the reaction liquid was qualitatively and quantitatively analyzed by gas chromatography using an internal standard method.

[0084] The product was quantitatively analyzed by the internal standard method. Biphenyl was used as the internal standard. A series of diphenyl carbonate standard solutions of different concentrations were accurately prepared. The internal standard was quantitatively added. The quantitative analysis was performed by the ratio of the response values ​​(peak area or peak height) of the standard solution and the internal standard during the response period and the amount of the internal standard added. Formula a was used to calculate the phenol conversion rate, and formulas b and c were used to calculate the selectivity and yield of the target product diphenyl carbonate. The calculation formulas are as follows:

[0085] a. Conversion rate (C)

[0086] C (%) = n (phenol conversion) / n (phenol initial) × 100

[0087] b. Selectivity (S)

[0088] S (%) = 2n (diphenyl carbonate) / n (phenol conversion) × 100

[0089] c. Yield (Y)

[0090] Y (%) = C (%) × S (%)

[0091] Where n is the amount of substance.

[0092] Table 1 - Catalytic performance evaluation results of Examples 1-7 and Comparative Examples

[0093]

[0094] The following conclusions can be drawn from Table 1:

[0095] 1) The catalytic performance of catalysts A1-A7 with different cerium contents under different pressures is compared. The test results are shown in Figures 6 to 8 .Depend on Figures 6 to 8 It can be seen that, compared with the catalytic performance of catalyst B1 without Ce element for the synthesis of diphenyl carbonate from phenol and carbon dioxide, it is found that when cerium is doped into zinc-zirconium solid solution, compared with catalyst B1, the catalytic performance of catalysts A1-A7 is significantly improved, with good phenol conversion rate, and high selectivity and yield for the target product diphenyl carbonate. Catalyst A1 has good diphenyl carbonate activity under 4MPa pressure conditions. When the Ce element doping content is further increased, the selectivity of diphenyl carbonate decreases.

[0096] 2) According to the comparison of catalysts A1-A4 in Table 1, the selectivity and yield of the target product diphenyl carbonate showed a gradually decreasing trend with the increase of cerium content. According to the comparison of catalysts A1, A5-A7, the selectivity and yield of the target product diphenyl carbonate showed a gradually decreasing trend with the increase of zinc content. The results show that catalyst A1 has the best catalytic performance.

[0097] Examples 8-10 are preparations of cerium-doped zinc-zirconium solid solution catalysts with different metal precursors:

[0098] Example 8

[0099] Weigh 5mmol of cerium nitrate hexahydrate, 5mmol of zinc nitrate hexahydrate, and 20mmol of zirconium chloride, dissolve them in 200mL of deionized water and stir them evenly to form a mixed solution with a metal ion concentration of 0.15mol / L. The other preparation steps are the same as those in Example 1 to obtain CeZnZr4O x Catalyst A8, wherein the molar ratio of Ce / (Zn+Zr) is 1:5.

[0100] Example 9

[0101] Weigh 5mmol of cerium nitrate hexahydrate, 5mmol of zinc sulfate heptahydrate, and 20mmol of hydrated zirconium oxynitrate, dissolve them in 200mL of deionized water and stir them evenly to form a mixed solution with a metal ion concentration of 0.15mol / L. The other preparation steps are the same as those in Example 1 to obtain a mixture with a molecular formula of CeZnZr4O x Catalyst A9, wherein the molar ratio of Ce / (Zn+Zr) is 1:5.

[0102] Example 10

[0103] Weigh 5mmol cerium chloride, 5mmol zinc sulfate heptahydrate, and 20mmol hydrated zirconium oxynitrate, dissolve in 200mL deionized water and stir evenly to form a mixed solution with a metal ion concentration of 0.15mol / L. The other preparation steps are the same as those in Example 1 to obtain a molecular formula of CeZnZr4O x Catalyst A10, wherein the molar ratio of Ce / (Zn+Zr) is 1:5.

[0104] Test Example 2

[0105] Catalysts A8-A10 obtained in Examples 8-10 were used to synthesize diphenyl carbonate from carbon dioxide and phenol, and the catalyst evaluation procedure was the same as that in Experimental Example 1.

[0106] Table 2-Evaluation results of catalytic performance of different metal salt precursors

[0107]

[0108] As shown in Table 2, the catalytic activity of catalysts prepared from different metal salt precursors for the synthesis of diphenyl carbonate from carbon dioxide and phenol is significantly different. Among the catalysts A1, A8-A10 in Table 2: the catalysts prepared from hexahydrated cerium nitrate, hexahydrated cerium zinc nitrate and hydrated zirconium oxynitrate compounds have the highest activity for the synthesis of diphenyl carbonate from carbon dioxide and phenol. - Compounds, therefore, there is no Cl on the catalyst - During the use of the catalyst, the catalyst surface is clean, which is another reason for the high activity of the catalyst.

[0109] Examples 11-14 are preparations of cerium-doped zinc-zirconium solid solution catalysts at different aging temperatures and times:

[0110] Embodiment 11

[0111] Weigh 5mmol hexahydrated cerium nitrate, 5mmol hexahydrated zinc nitrate, and 20mmol hydrated zirconium oxynitrate, dissolve in 200mL deionized water and stir evenly to form a mixed solution with a metal ion concentration of 0.15mol / L. After stirring for 0.5h in a 70°C water bath, 25wt% ammonia water is slowly added to the precursor solution, and the pH value of the aqueous solution is adjusted to 11. After the addition is completed, keep it in a 70°C water bath for aging for 2h. The other preparation steps are the same as in Example 1, and the molecular formula CeZnZr4O is obtained. x Catalyst A11, wherein the molar ratio of Ce / (Zn+Zr) is 1:5.

[0112] Example 12

[0113] Weigh 5mmol hexahydrated cerium nitrate, 5mmol hexahydrated zinc nitrate, and 20mmol hydrated zirconium oxynitrate, dissolve in 200mL deionized water and stir evenly to form a mixed solution with a metal ion concentration of 0.15mol / L. After stirring for 0.5h in a water bath at 80°C, 25wt% ammonia water is slowly added to the precursor solution, and the pH value of the aqueous solution is adjusted to 11. After the addition is completed, keep it in a water bath at 90°C for aging for 2h. The other preparation steps are the same as in Example 1, and the molecular formula CeZnZr4O is obtained. x Catalyst A12, wherein the molar ratio of Ce / (Zn+Zr) is 1:5.

[0114] Embodiment 13

[0115] This embodiment provides a CeZnZrO X -13 preparation method, comprising the following steps:

[0116] Weigh 5mmol hexahydrated cerium nitrate, 5mmol hexahydrated zinc nitrate, and 20mmol hydrated zirconium oxynitrate, dissolve in 200mL deionized water and stir evenly to form a mixed solution with a metal ion concentration of 0.15mol / L. After stirring for 0.5h in a water bath at 80°C, 25wt% ammonia water is slowly added to the precursor solution, and the pH value of the aqueous solution is adjusted to 11. After the addition is completed, keep it in a water bath at 80°C for aging for 3h. The other preparation steps are the same as in Example 1, and the molecular formula CeZnZr4O is obtained. x Catalyst A13, wherein the molar ratio of Ce / (Zn+Zr) is 1:5.

[0117] Embodiment 14

[0118] This embodiment provides a method for preparing CeZnZrO2-14, comprising the following steps:

[0119] Weigh 5mmol hexahydrated cerium nitrate, 5mmol hexahydrated zinc nitrate, and 20mmol hydrated zirconium oxynitrate, dissolve in 200mL deionized water and stir evenly to form a mixed solution with a metal ion concentration of 0.15mol / L. After stirring for 0.5h in a water bath at 80°C, 25wt% ammonia water is slowly added to the precursor solution, and the pH value of the aqueous solution is adjusted to 11. After the addition is completed, keep it in a water bath at 80°C for aging for 4h. The other preparation steps are the same as in Example 1, and the molecular formula CeZnZr4O is obtained. x Catalyst A14, wherein the molar ratio of Ce / (Zn+Zr) is 1:5.

[0120] Embodiment 15

[0121] This embodiment is basically the same as embodiment 1, except that the aging time is 1 hour. The molecular formula is CeZnZr4O x Catalyst A15.

[0122] Example 16

[0123] This embodiment is basically the same as embodiment 1, except that the aging temperature is 50°C. The molecular formula is CeZnZr4O x Catalyst A16.

[0124] Test Example 3

[0125] The catalysts obtained in Examples 11-14 were used to synthesize diphenyl carbonate from carbon dioxide and phenol, and the catalyst evaluation procedure was the same as that in Experimental Example 1.

[0126] Table 3 - Effect of different aging temperatures and times on catalytic performance

[0127]

[0128] According to Table 3, the selectivity and yield of diphenyl carbonate first increase and then decrease with the aging temperature, and the catalyst prepared at an aging temperature of 80°C has better catalytic activity. The effect of aging time on catalytic activity was investigated in catalysts A1, A13, and A14, and the catalyst prepared at an aging time of 2h has better activity.

[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A cerium-doped zinc-zirconium solid solution catalyst, characterized in that: The chemical formula of the catalyst is Ce a Zn b Zr c O x , where 0≤a≤4, 1≤b≤4, c=4; The catalyst has a 2θ value of 28.46 o ~30.48 o The first diffraction peak, 2θ is 47.50 o ~50.81 o The second diffraction peak, 2θ is 56.27 o ~60.43 o The third diffraction peak, and 2θ is 32.98 o ~35.42 o The fourth diffraction peak of the optical spectrum is as follows, and the intensity ratio of the first diffraction peak, the second diffraction peak, the third diffraction peak and the fourth diffraction peak is (2.2-3.1):(1.1-1.4):(0.9-1.2):

1.

2. The catalyst according to claim 1, characterized in that The catalyst is prepared by a method comprising the following steps: The pH value of the aqueous solution including Ce, Zn and Zr elements is adjusted to be greater than or equal to 10, the obtained mixed system is subjected to aging treatment and solid-liquid separation treatment in sequence, and the obtained solid phase product is subjected to calcination treatment to obtain the catalyst.

3. A method for preparing the cerium-doped zinc-zirconium solid solution catalyst according to claim 1 or 2, characterized in that: The steps include: The pH value of the aqueous solution including Ce, Zn and Zr elements is adjusted to be greater than or equal to 10, the obtained mixed system is subjected to aging treatment and solid-liquid separation treatment in sequence, and the obtained solid phase product is subjected to calcination treatment to obtain the catalyst.

4. The preparation method according to claim 3, characterized in that: The molar ratio of Ce / (Zn+Zr) is 0.125-0.8; and / or, In the aqueous solution, the concentration of total metal elements is 0.150-0.225 mol / L.

5. The preparation method according to claim 3 or 4, characterized in that: The pH value of the aqueous solution including the Ce element, the Zn element and the Zr element is adjusted to 10-11.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The treatment temperature of the aging treatment is 70-90° C., and the treatment time is 2-4 hours.

7. The preparation method according to any one of claims 3 to 6, characterized in that: The calcination treatment has a treatment temperature of 500-600° C., a treatment time of 2-4 hours, and a heating rate of 1-3° C. / h.

8. The preparation method according to any one of claims 3 to 7, characterized in that: Before the solid phase product is calcined, the solid phase product is dried at a temperature of 100 to 120° C. for a time of 6 to 10 hours.

9. A method for preparing diphenyl carbonate, characterized in that: The catalyst according to claim 1 or 2 is used to catalyze the reaction of carbon dioxide and phenol to obtain diphenyl carbonate.

10. The method for preparing diphenyl carbonate according to claim 9, characterized in that: The reaction temperature of the reaction is 90-130° C., the reaction pressure is 1-5 MPa, and the reaction time is 4-8 hours.

Citation Information

Patent Citations

  • Copper-doped ZnO-ZrO2 sosoloid catalyst and preparing method and application thereof

    CN109621965A

  • Temperature tunable mesoporous gold deposited co oxidation catalyst

    WO2015063797A1